Revisiting the foreign debt problem and the "external constraint" in the periphery: An MMT perspective - Ndongo Samba Sylla (Levy Economics Institute of Bard College, 2024)
Most debates and policy proposals about Global South countries' external debt problem take for granted the view that it is normal for their governments to issue debts denominated in foreign currencies. This paper tries to challenge this widely held and usually unquestioned assumption by relying on Modern Money Theory (MMT) insights. The author argues that the MMT lens helps us understand the root causes of the foreign debt problem of Southern countries, those located in Africa in particular, to clarify the ordinarily mis-specified concept of "external constraint" or "balance-of-payments constraint" and to envisage progressive domestic policy measures that are under their control.
Keywords: 330